PENGARUH BIAYA PRODUKSI, TOTAL HUTANG DAN MODAL KERJA TERHADAP LABA BERSIH PADA PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA 2018 - 2021 - Ahmad Qhoirul; Ahsan Putra Hafiz; Achyat Budianto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Profit is one type of financial information that attracts the attention of investors. The ability to generate maximum profits in a company is very important because basically interested parties, such as investors and creditors, measure the company's success based on the company's ability as seen from management's performance in generating profits in the future. Getting optimal profits is not an easy thing, because profits can also be influenced by the amount of existing capital, both own capital and debt, and ongoing sales which can make profits large or small. This research aims to analyze the influence of production costs, total debt and working capital on net profit in consumer goods companies listed on the IDX for the 2018-2021 period. The sample used in this research was 13 consumer goods companies registered on the IDX for the 2018-2021 period by going through the purposive sampling stage in accordance with the criteria required for the research. The data analysis method in this research uses panel data regression techniques. The research results show that production costs, total debt and working capital have an influence on net profit, with an influence of 21.65%, while the remaining 78.25% is explained by other variables outside the research.